Мінливість морфологічних ознак Salvia officinalis L. при інтродукції - Gorlacheva, Z.S.; Kustova, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
Research of variability of the morphological characters of Salvia officinalis L. showed the high level of variability of vegetative characters, low variability of generative characters and reproductive indexes.